Product innovation in a vertically differentiated model - Luigi Filippini; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
We study the licensing incentives of an independent input producer owning a patented product innovation which allows the downstream firms to improve the quality of their final goods. We consider a general two-part tariff contract for both outside and incumbent innovators. We find that technology diffusion critically depends on the nature of market competition (Cournot vs. Bertrand). Moreover, the vertical merger with either downstream firm is always privately profitable and it is welfare improving for large innovations: this implies that not all profitable mergers should be rejected.
Keywords: L15; L13; L24; 330